A note on the laboratory culture of the benthic foraminifer Cornuloculina balkwilli (MacFadyen) - Seears, Heidi A.; Wade, Christopher M. (BioMed Central, 2013)
Background: Genetic studies of the Foraminifera provide valuable insights into marine speciation and biogeography, yet the discovery of vitally needed new genetic markers for this important group is being severely limited by an extreme lack of genetic data. The establishment of a laboratory culture from a single, asexually reproducing foraminifer, will be essential to provide enough pooled genetic material from these unicellular organisms, to facilitate full genome sequencing and genetic marker discovery, using next-generation sequencing techniques.